2013
DOI: 10.12659/msm.889479
|View full text |Cite
|
Sign up to set email alerts
|

Current status of percutaneous vertebroplasty and percutaneous kyphoplasty – a review

Abstract: Percutaneous vertebroplasty (PV) and kyphoplasty (PK) are the 2 vertebral augmentation procedures that have emerged as minimally invasive surgical options to treat painful vertebral compression fractures (VCF) during the last 2 decades. VCF may either be osteoporotic or tumor-associated. Two hundred million women are affected by osteoporosis globally. Vertebral fracture may result in acute pain around the fracture site, loss of vertebral height due to vertebral collapse, spinal instability, and kyphotic deform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(23 citation statements)
references
References 123 publications
(122 reference statements)
0
22
0
1
Order By: Relevance
“…50,51 Bioactive composite materials prepared from acrylic cement in conjunction with ceramics showed good radioopacity. 52 Cortoss, a composed material-based bone cement currently undergoing clinical trials for PVP and BKP is composed of terpolymer resin with combeite glass-ceramics.…”
Section: Anatomy and Physiopathologymentioning
confidence: 99%
“…50,51 Bioactive composite materials prepared from acrylic cement in conjunction with ceramics showed good radioopacity. 52 Cortoss, a composed material-based bone cement currently undergoing clinical trials for PVP and BKP is composed of terpolymer resin with combeite glass-ceramics.…”
Section: Anatomy and Physiopathologymentioning
confidence: 99%
“…Vertebroplasty and kyphoplasty are the most routinely used minimally invasive procedures to treat VCF during last two decades 8. Clinical studies have reported no difference in the outcome of pain relief and quality of life improvement between PVP and penetrating keratoplasty (PKP) 910.…”
Section: Discussionmentioning
confidence: 99%
“…In PK, a balloon is inserted into the fractured site and inflated-deflated to create a cavity: the balloon is then taken out prior to cement injection. Both procedures are superior to oral pain management: no direct comparison is available but systematic reviews of the existing data showed very little difference in clinical outcomes of the 2 techniques [73]. The overall rate of complications associated with PV and PK is low, but the rate of cement extravasation is higher in PV.…”
Section: Local Treatment Of Selected Disease Sitesmentioning
confidence: 99%
“…The overall rate of complications associated with PV and PK is low, but the rate of cement extravasation is higher in PV. PV of painful osteolytic spinal metastases from BC is safe even in the case of substantial involvement of the vertebral cross-sectional area or cortical bone [73,74]. To establish the relative strengths and weaknesses of all these procedures, well-designed randomized clinical trials are required.…”
Section: Local Treatment Of Selected Disease Sitesmentioning
confidence: 99%